INTEGRATION OF LOCAL VALUES IN HISTORY LEARNING AT SMA NEGERI 5 MEDAN - Hidayat, Muhammad Abdi; Nasution, Abd. Haris; Nasution, Soviannur (Puteri Hijau : Jurnal Pendidikan Sejarah, 2025)
This research is titled "Integration of Local Values in History Learning at SMA Negeri 5 Medan" and aims to identify how local cultural values are integrated into history learning and understand the challenges and impacts on students. The research method used is qualitative with a descriptive approach. Data was collected through in-depth interviews, observations, documentation studies, and focus group discussions (FGDs) with teachers, students, principals, and community leaders. The results of the study show that teachers have made efforts to integrate local values through methods such as folklore and local history case studies. However, the challenges faced include limited teaching materials, lack of teacher training, and a dense curriculum load. Although students show high interest and feel more engaged when local values are incorporated into learning, this integration has not been fully optimal and consistent. This research emphasizes the importance of developing a more contextual curriculum, more in-depth teacher training, and collaboration with local communities. The integration of local values is expected to strengthen students' cultural identities and preserve local cultural heritage, with a significant impact on their character formation and historical understanding.